Impact of Mind Gardens Strategy on Long Distance Shooting in U16 Basketball - Mahmood, Raheeq; Jabar , Ammar (Indonesian Journal Publisher, 2024)
The study conducted in order to analyze the role of the Mind Gardens Strategy to develop long distance shooting from the basketball players in under 16 age group. 24 subjects from a local basketball club were randomly assigned to two groups: the experimental group trained by the Mind Gardens Strategy and the control group trained in the traditional way. There were three main tests in the experiment: the Five-Area Shooting Test, the Long-Distance Shooting Speed and Accuracy Test, and the Long-Distance Shooting Under Pressure Test. The results showed that the experimental team achieved performances significantly superior in the three tests, being those related to the capacity of shooting more accurate, faster and with higher success under pressure. The experimental group showed significant increases in shooting accuracy (23.93%), and shooting speed and accuracy (33.28%), and performance under pressure (34.58%). On the other hand, the control group showed less significant developments, highlighting the effectivity of Mind Gardens Strategy in the development of shooting performance when compared to the traditional one. These results indicate that the exercise employing dual cognitive training schemes, such as the Mind Gardens Strategy, on basketball training program may be useful for improving long-range shooting performance. The study highlights the relevance of cognitive tactics in sports coaching, especially among young persons involved in sports.